Performance comparison of active suspension for ride comfort using linear quadratic regulator and fuzzy logic controller / Muhammad Hazwan Harun - Harun, Muhammad Hazwan (2018)
The main purpose of a suspension is to reduce the vibration that occurs when driving on the road. However, this vibration still exists in passive suspension which contain high frequency causing reduced ride comfort and road handling. Besides that, the effects of using the passive suspension also cause damage to certain component of cars when passing through holes in the road and also when there is a high bump. To overcome this problem, a comparison has been made based on the performance between passive suspension, Linear Quadratic Regulator (LQR) and Fuzzy logic Controller (FLC) that use specific parameters based on previous studies. This investigation focus on 2 degree of freedom (DOF) quarter car suspension using the MATLAB / SIMULINK toolbox. Several road profiles were used and analysis based on car body displacement, car body acceleration, suspension travel and space rattle was carried out. The results of the analysis show that both controllers can reduce vibration. However, FLC provides the best performance compared to LQR.